THE EFFECTIVENESS OF MY POCKETBOOK TO IMPROVING WRITING SKILLS OF INTEGRATED ISLAMIC ELEMENTARY SCHOOLS CHILDREN IN YOGYAKARTA - Albi Anggito; Hana Ika Safitri; Harun Harun; Ali Mustadi (Al-Bidayah : jurnal pendidikan dasar Islam, 2021)
This research is based on the problem of students' writing skills in elementary schools which are still very low. This research aims to determine the effectiveness of "my pocketbook" in improving the writing skills of children of Integrated Islamic elementary school in Yogyakarta. This research uses a quasi-experimental design with pretest and postest group design. The samples were used with the technique of simple random sampling. This research analyzed 30 students from one of the elementary schools in the Sanden District as the samples of the study due to limited time and research costs. The data collection technique used by researchers is observation. The results of the conducted research were analyzed using the T test in SPSS 21 software base observation. The result of the research shows that the hypothesis is accepted. In other words, "my pocketbook" is effective of Sig. (2-tailed) that is 0.00 improve the writing skills of the student at Integrated Islamic elementary schools in Yogyakarta. It can be seen from the result of Sig. (2-tailed) that is 0.00. The less than 0.05 result indicates that the hypothesis is accepted. The research concludes that my pocketbook is effective for improving the writing skills of the children of integrated Islamic elementary schools in Yogyakarta. The results of this study are expected to be an alternative media in training students' writing skills as well as being a reference for future research.